<span>Simplifying
3x + -1y = 12
Solving
3x + -1y = 12
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'y' to each side of the equation.
3x + -1y + y = 12 + y
Combine like terms: -1y + y = 0
3x + 0 = 12 + y
3x = 12 + y
Divide each side by '3'.
x = 4 + 0.3333333333y
Simplifying
x = 4 + 0.3333333333y</span>
3/10 times 2/3 3 times 2 is 5 and 10 times 3 is 30 5/30 a
<span>42.7−<span>(<span>−12.4</span>)
</span></span><span>=<span>42.7−<span>(<span>−12.4</span>)
</span></span></span><span>=<span>42.7+12.4
</span></span><span>=<span>55.1</span></span>
Answer:
I think the answer is C
Step-by-step explanation: